PTH-031 Is flexible sigmoidoscopy in the setting of normal computer tomographic colonography necessary?. (June 2019) - Johal, Harleen; Hartery, Karen; Kale, Vikrant; Cheung, Vincent; Koutsounis, Ioannis; Ferrett, Colin; Bailey, Adam
Abstract : Introduction: The demand to deliver rapid diagnosis of colorectal cancer (CRC) safely and effectively continues to increase. The practice of combining flexible sigmoidoscopy (FS) and CT colonography (CTC) has been driven by a concern that CTC misses some rectosigmoid cancers. NICE guidelines state that CTC can be considered as an alternative to colonoscopy for diagnosis, if a radiology service can demonstrate competency in this technique. The Oxford University Hospitals Foundation Trust OUHFT two-week wait (2WW) referral pathway for suspected CRC states that patients over 75 years, or over 60 years with chronic medical co-morbidities and symptoms suspicious of CRC should have both FS and CTC (with low dose prep for frail patients). The aim of this audit was to assess the additional cancer yield of FS in the setting of normal CTC. Methods: Analysis of all referrals (n=941) meeting the above criteria over a thirteen-month period (July 2015 – August 2016) was performed. Of these referrals, 851 CTCs were reviewed and 901 FSs. Endoscopic data was obtained from reports, including findings, bowel preparation, study quality, level reached, reasons for failure and histopathology. Radiological data was obtained from CTC reports, taking into account the findings, technique, study quality and recommendations. The two data sets were then directly compared, with particular focus on the correlation between CTC and FS when identifying left-sided CRC. Results: 37 L-sided CRCs were identified on FS. The splenic flexure was only reached in 22.1% (n=200) of the studies, with poor bowel preparation being the most frequently documented reason for failure. 87 possible CRCs were identified on CTC. Of these, 34 were right-sided CRCs, 9 were left-sided suspicious polyps, and 44 were left-sided CRCs. When correlating the radiology, histopathology and endoscopic findings, there were 7 CRCs identified on CTC that were not seen on FS. Of these, 4 were histologically proven to be CRCs that were missed due to incomplete endoscopic procedure. By comparison, only one 20 mm polyp, a lateral spreading tumour (LST) seen on FS was missed on CTC. 447 CTCs (52.5%) were reported as showing benign colonic disease (e.g. diverticular disease, small polyps) and further endoscopic evaluation was advised in 27.7% (n=124). Conclusion: We demonstrated that all CRCs seen on FS were identified on CTC. In the setting of normal CTC, only 1 LST was missed. By amending the OUHFT 2WW referral pathway, so that CTC is completed first, with subsequent endoscopic evaluation only if the CTC is inconclusive or the reporting radiologist recommends direct visualisation, we anticipate substantial resource saving without compromising diagnostic performance for colorectal cancer.